HEPATOPROTECTIVE PROPERTIES OF SELECTED PLANTS AGAINST PARACETAMOL-INDUCED HEPATOTOXICITY IN MICE (Journal of Institute of Science and Technology, 2017)
The hepatoprotective properties of the ethanolic extracts of Punica granatum peels, Crataeva religiosa leaves and Jasminum polyanthrum leaves were evaluated for the paracetamol induced liver toxicity in mice. Antioxidant, cytotoxicity and phytochemical screening were carried out to assure the therapeutic efficacy of these plants. Oral administration of plant extracts for 7 days in mice significantly reduced the impact of paracetamol toxicity on the serum markers of liver damage, aspartate transaminase (AST), alanine transaminase (ALT) and total protein. The extract showed significant hepatoprotective effects as evidenced by decreased serum enzyme activities like ALT, AST and changed total protein. The phytochemical and antioxidant studies also supported that plant extract markedly reduced the toxicity due to presence of antioxidant phytochemicals. The result suggests that Jasminum polyanthrum is potent hepatoprotective agent against paracetamol induced hepatotoxicity in mice.Journal of Institute of Science and TechnologyVolume 22, Issue 1, July 2017, Page: 147-151